2016
DOI: 10.1051/parasite/2016070
|View full text |Cite
|
Sign up to set email alerts
|

Relative importance of meteorological and geographical factors in the distribution ofFasciola hepaticainfestation in farmed sheep in Qinghai province, China

Abstract: Fasciola hepatica is an important trematode parasite of economic importance that infests sheep and cattle worldwide. We conducted a detailed investigation into the spatial distribution of F. hepatica infestation in farmed sheep in Qinghai (Wutumeiren) province, Mainland China. Mathematical modelling was used to assess the inter-relationships between meteorological and geographical factors and the risk of F. hepatica infestation across the province. A capture enzyme-linked immunosorbent assay (ELISA) test (MM3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 34 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…Bennema et al (2011) reported that annual rainfall is a positive predictor of infection in Belgium, and McCann et al (2010a, b) found the same for dairy herds in England and Wales. An analysis by Qin et al (2016) similarly reported that temperature, rainfall and elevation were associated with F. hepatica infestation in China. Climate conditions impact the development and distribution of the parasite's intermediate molluscan and free-living stages.…”
Section: Discussionmentioning
confidence: 99%
“…Bennema et al (2011) reported that annual rainfall is a positive predictor of infection in Belgium, and McCann et al (2010a, b) found the same for dairy herds in England and Wales. An analysis by Qin et al (2016) similarly reported that temperature, rainfall and elevation were associated with F. hepatica infestation in China. Climate conditions impact the development and distribution of the parasite's intermediate molluscan and free-living stages.…”
Section: Discussionmentioning
confidence: 99%
“…In China, temperature, rainfall and elevation have been associated with F . hepatica infestation (Qin et al ., 2016). Temperatures greater than 10°C are required for the development of the free-living larval stages and intra-snail stages of the trematode, as well as the development of the parasite's intermediate molluscan (Andrews et al ., 1999; Torgerson & Claxton, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Economic losses in the livestock industry exceed USD 3 billion worldwide, including USD 119 million per year in the Mexican cattle industry (Mehmood et al ., 2017; Villa-Mancera & Reynoso-Palomar, 2019b). Infected animals show reduced weight gain, fertility and meat and milk production, as well as liver condemnation in abattoirs, although this condition rarely causes mortality in cattle (Torgerson & Claxton, 1999; Sanchez-Vazquez & Lewis, 2013; Qin et al ., 2016). In Mexico, several recent studies using bulk-tank milk enzyme-linked immune sorbent assay (ELISA) in cattle herds have indicated that the F .…”
Section: Introductionmentioning
confidence: 99%
“…Temperature, water and snail are important factors in the epidemicity of F. hepatica . At the same time, rainfall has a positive effect on the development of F. hepatica and reproduction of the snail intermediate host (Mas-Coma et al, 2009; Novobilsky et al, 2014; Qin et al, 2016). The present study confirmed 87.35% prevalence of F. hepatica infections in buffaloes on 58 farms from 8 districts in Guangxi, this is consistent with the results of F.gigantica in Guangxi reported by Passi et al (2009, in Chinses).…”
Section: Discussionmentioning
confidence: 99%